Karakteristik Budaya Organisasi Islam sebagai Upaya Peningkatan Kinerja di Universitas Muhammadiyah Malang - Sri Budi Cantika Yuli (Universitas Islam Raden Rahmat, 2021)
This study aims to reveal the characteristics of Islamic organizational culture at University of Muhammadiyah Malang as an effort to improve employee performance. This study uses qualitative method by applying phenomenology approach. It is conducted by examining the experience realized by the informant (conscious experience) and the instruments of data collection are interviews, observation, and documentation so that researchers can obtain more complete data about the characteristics of Islamic organization culture at University of Muhammadiyah Malang. The research subjects are: (1) university board; (2) deans; (3) employees. Moreover, the qualitative data analysis techniques in this study uses 3 (three) analyzes, namely: data reduction, data presentation, and conclusion. The results of this study indicate that perceptions of Islamic organizational culture can be seen from the perception of university board, lecturers and employees on the value of leadership, norms and management practices, stories and figures, traditions and rituals, as well as perceptions on symbols. It can be concluded that the characteristics of Islamic organizational culture include: (1) Shiddiq (truthfulness) to achieve personal excellence that is honest, transparent, and accountable, (2) Amanah (trustworthiness) to achieve inter-personal capital that is unprejudiced and commitment, (3) Tabligh (advocacy) to achieve visionary and communicative leadership that is communicative and open, (4) Fathonah (wisdom) to achieve professionalism and technical leadership that is smart, competent, and innovative.